MANAJEMEN SARANA DAN PRASARANA DI ERA DIGITAL DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI MTs NEGERI 2 PESAWARAN - Satya Pirnando; Ahmad Fauzan; Prima Aji Putra (STKIP Pesisir Selatan, 2026)
The rapid development of digital technology has required educational institutions to adopt adaptive management of facilities and infrastructure to enhance learning quality. This study aims to examine the management of digital-based educational facilities and infrastructure and its impact on the learning process at MTs Negeri 2 Pesawaran. A descriptive qualitative approach with a field research design was employed. Data were collected through direct observation, in-depth interviews with the principal, vice principal for facilities and infrastructure, teachers, educational staff, and students, as well as documentation analysis related to facility management. The scope of the study includes planning, procurement, distribution, inventory, maintenance, and disposal of digital facilities and infrastructure. Data were analyzed using data reduction, data display, and conclusion drawing, supported by triangulation techniques to ensure data validity. The findings reveal that the management of facilities and infrastructure at MTs Negeri 2 Pesawaran has shown significant improvement through the utilization of digital resources such as projectors, computers, laptops, internet networks, and digital administrative systems.